2015
DOI: 10.1074/jbc.m115.638221
|View full text |Cite
|
Sign up to set email alerts
|

Pim-2 Kinase Influences Regulatory T Cell Function and Stability by Mediating Foxp3 Protein N-terminal Phosphorylation

Abstract: Background: Foxp3 activity is regulated by various posttranslational modifications. Results: Pim-2 kinase phosphorylates the Foxp3 N-terminal domain and influences the Foxp3 level in vivo. Conclusion: Pim-2 is a negative regulator of Foxp3 activity. Significance: Phosphorylation of Foxp3 by Pim-2 kinase negatively regulates Treg cell suppressive function and stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 46 publications
0
58
1
Order By: Relevance
“…IL-9/IL-9R signal- late Foxp3 and negatively regulate Treg suppressive function and stability (22). However, these studies did not distinguish between the roles of PIM-2 kinase on natural Tregs (nTregs) and iTregs.…”
Section: Pim-2-deficient T Cells Augment Antitumor Activity Via Il-9rmentioning
confidence: 87%
See 1 more Smart Citation
“…IL-9/IL-9R signal- late Foxp3 and negatively regulate Treg suppressive function and stability (22). However, these studies did not distinguish between the roles of PIM-2 kinase on natural Tregs (nTregs) and iTregs.…”
Section: Pim-2-deficient T Cells Augment Antitumor Activity Via Il-9rmentioning
confidence: 87%
“…PIM-1 and PIM-2 kinases are required for rapamycin resistance upon T cell activation; therefore, the lack of these kinases in vivo has been shown to promote rapamycin sensitivity (21). In addition, the previous report demonstrated that the phosphorylation of Foxp3 by PIM-2 kinase decreased suppressive functions of regulatory T cells (Tregs) (22). In contrast, PIM-2 kinase was previously shown to act as a negative regulator of suppressor of cytokine signaling 1 (SOCS-1) in T cells, and the phosphorylation protects SOCS-1 from degradation (23).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, deficiency of Pim-2 activity increased murine host resistance to DSS-induced colitis and a small molecule kinase inhibitor for Pim-2 also modified Treg functions. 30 It was reported that the over-expression of Stub1 could activate Akt and inhibit the FoxO transcription factors FoxO1, FoxO3, and FoxO4. Inhibition of PI3K by an antagonist revealed that these events may be critical for Stub1-induced apoptosis resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In human T reg cells, PIM2 interacts with FOXP3 and targets multiple N-terminal sites (S33, S41 and a third unspecified site). Through an as yet unknown mechanism, PIM2 interferes with the expression of T reg cell-associated genes, and the inhibition of PIM2 in mouse T reg cells increases their suppressive capabilities 97 . Interestingly, PIM2 expression has been reported to be FOXP3 dependent and involved in the expansion of T reg cells 98 .…”
Section: Post-translational Modification Of Foxp3mentioning
confidence: 99%